(untitled) (Academicia Globe: Inderscience Research, 2023)
In recent years, many developed countries prefer the use of drugs based on natural products instead of synthetic drugs in the treatment of various diseases. The demand for high-quality food and medicines is increasing year by year in our Republic, whose nature has been rich in healing blessings since ancient times [1]. - As stated in the decision of the Cabinet of Ministers on "Receive state protection of medical and drug production industries of the Republic of Uzbekistan" (1996), preservation of medicinal plants growing in the local flora and growing in the wild, as well as acclimatization and breeding of medicinal plant species that are not found in the flora of Uzbekistan, are special paying attention is one of the important issues today [6]. In this article, the germination of the seeds of Galega officinalis L., which is considered a medicinal plant, is studied.